Diagnostic markers for glioblastoma - Jung, Carla Sabine; Unterberg, Andreas; Hartmann, Christian (Histology and histopathology, 2011)
Glioblastoma (GBM) is the most malignant form of cerebral gliomas, and despite distinct progress in surgical resection, radiation and chemotherapy, the prognosis of patients with GBM is still very poor. In the past decades knowledge of genomics and proteomics and of diagnostic, prognostic, predictive and pharmakodynamic markers measured in cerebrospinal-fluid (CSF), serum, or tumor tissue biomarkers has improved. This review briefly compiles our concepts on diagnostic markers for GBM, focusing on the latest developments
Gesehen am 05.07.2022